THE READABILITY LEVEL OF READING TEXTS IN THE ENGLISH LANGUAGE TEXTBOOKS USED BY THE TENTH GRADE - IKA RAHMAWATI, YULY (RETAIN : Journal of Research in English Language Teaching, 2014)
Memprediksi tingkat keterbacaan teks dapat membantu guru untuk menyesuaikan teks dengan tingkatan siswa. Teks bacaan yang sesuai diharapkan dapat mempermudah siswa dalam memahami materi. Teks bacaan untuk siswa SMA terdiri dari naratif, deskriptif, teks berita, dan recount.Tujuan penelitian ini adalah untuk mencari dan membandingkan tingkat keterbacaan teks bacaan dalam buku bahasa Inggris yang digunakan oleh siswa kelas sepuluh. Penelitian ini juga menguji apakah tingkat keterbacaan teks bacaan dalam buku-buku bahasa Inggris telah sesuai dengan tingkatan siswa kelas sepuluh. Penelitian ini menggunakan pendekatan deskriptif untuk menganalisa data yang ada. Teks bacaan diambil dari dua buku bahasa Inggris; “Developing English Competencies for Grade X” yang diterbitkan oleh Departemen Pendidikan Nasional (awalnya diterbitkan dalam format buku elektronik) dan “English Today 1” yang diterbitkan oleh penerbit Quadra. Enam teks dengan jenis yang berbeda dipilih dari masing-masing buku bacaan. Semua teks yang telah dipilih kemudian dianalisa dengan menggunakan formula Flesch Reading Ease dan Grafik Fry. Kedua formula menunjukkan bahwa sebagian besar teks bacaan berada pada level ketujuh. Hal itu menunjukkan bahwa bacaan-bacan tersebut mudah dibaca oleh siswa kelas sepuluh. Dalam penelitian ini juga ditemukan bahwa “English Today 1” memiliki teks bacaan dengan tingkat kesulitan yang lebih tinggi dibandingkan dengan “Developing English Competencies for grade X”. Dengan kata lain, teks bacaan yang terdapat pada buku “English today 1” lebih menantang bagi siswa sehingga guru harus memberikan lebih banyak bimbingan pada sesi membaca. Kata kunci: Keterbacaan, Developing English Competencies for Grade X, English Today 1 Abstract Predicting readability level of reading texts can help the teachers to match the texts with students’ grade. The appropriate reading text is expected to ease the students in comprehending the material. Reading texts for Senior High School students consists of narrative, descriptive, news item, procedure, and recount. The purpose of this study is to find and compare the readability level of reading texts in English language textbooks used by the tenth grade students. The study also verify whether the reading materials of the textbooks have matched the grade level of the tenth grade students. This research used descriptive approach to analyze the data. The reading texts were taken from two English language textbooks; “Developing English Competencies for Grade X” published by the Department of National Education (originally published in the form of electronic book) and “English Today 1” published by Quadra. Six texts with different type are selected from each textbook. All of selected texts are analyzed by using Flesch Reading Ease formula and Fry Graph formula. Both formulas show that the reading texts mostly appear on 7th level. It indicates that the texts are easily to be read by tenth grade students. The study also found that “English Today 1” has some texts with higher difficulty level than “Developing English Competencies for grade X”. In other words, the reading texts in “English Today is more challenging for the students so that the teacher should give more guidance in reading session. Keywords: Readability, Developing English Competencies for Grade X, English Today